Sport Events and Residential Happiness: The Case of Two Non-Mega Sport Events. Issue 3 (1st October 2016) - Taks, Marijke; Littlejohn, Meagan; Snelgrove, Ryan; Wood, Laura
ABSTRACT: This contribution explores whether the hosting of two non-mega sport events affected the happiness of residents (non-attendees) in the host community, and if these feelings differed according to the type of event. The events under investigation were two multi-sport events held in the same community during the summer of 2014: the Ontario Summer Games and the 55+ Summer Games. Residents were intercepted in public spaces to complete a survey, including levels of happiness, event, and socio-demographic variables. Happiness was measured in a holistic way, including overall happiness, satisfaction, positive and reversed negative affect dimensions of subjective well-being. Hierarchical regression analysis revealed: (1) higher levels of happiness for aware, non-attendee residents when measured with a single item of overall happiness, but not for other measures of happiness in the holistic approach (causality cannot be confirmed); (2) aware, non-attendee residents did not need to have the intention to attend the events to experience these higher levels of happiness; and (3) higher feelings of happiness of aware, non-attendee residents were not different according to the type of event. From a practical perspective, these findings stress the importance of informing residents of these events so they become aware that these events are being hosted in their community. Effective communication should include feelings of pride and belonging, as these are expected to stimulate feelings of happiness of non-attendee residents.